Pengaruh Lama Fermentasi Dan Jenis Sumber NitrogenTerhadap Produktivitas Dan Sifat Fisik Nata De Lontar(Borassus flabellifer) - Hastuti, Anisa Indriana Tri, Dr. Nanik Prihartanti, M.Si (2015)
Nata was food which is produced from the fermentation process of coconut water that has white color, clear and chewy-textured. Nata formed from Acetobacter xylinum bacterial activity. The aims of the research was to investigate the of nata productivity and physical characteristic of nata de lontar with variation of fermentation duration and different of nitrogen. This research was using Randomized Complete Design (RAL) factorial with two factors. The first factor was days of fermentation process (5, 10, and 15 days). The results showed the longer the fermentation nata de papyrus then thick and heavy nata de ejection tends to increase and inversely proportional to the residual liquid fermentation, soy sprouts N sources of nata de lontar produce the most, nata de lontar with N sources soybean sprouts fermentation 15 days has a thickness of 1.22 cm, weight 165 g, the rest of the fermentation liquid 300 ml and pH 3.